Measles humoral immunity in health-care workers - E. A. Krieger (Infekciâ i Immunitet, 2021)
Healthcare-workers are at risk of contact with measles patients and disease transmission. Measles-infected employees of healthcare facilities may contribute to the nosocomial measles spread and serve as a source of infection for most susceptible cohorts such as pregnant women, neonates, and immunocompromised patients. In order to study the humoral immunity against measles in healthcare workers and reveal factors associated with seronegative status, we performed a cross-sectional study by enrolling 847 healthcare workers of the Arkhangelsk Regional Clinical Hospital. Anti-measles virus serum immunoglobulin G antibodies were quantified by using VectorMeasles-IgG ELISA kit (Vector-Best, Russia). According to the manufacturer's recommendations specific IgG anti-measles titer cut-off value higher than 0.18 IU/ml, equal to 0.12—0.17 IU/ml, or lower than 0.12 IU/ml was considered as positive (protective), equivocal, or negative, respectively. Assessing an impact of employee's gender, age, affiliation (department), current position was carried out by using binary logistic regression analysis while analyzing seronegative status of healthcare workers. Study participants dominated by females (92.1%). The median age was 48 (39; 57) years. The employees of somatic departments prevailed (26.7%). It was found that 93.7% of medical workers had concentration of anti-measles antibodies exceeding magnitude of protective titer (above 0.18 IU/ml), 4.4% and 1.9% were measles seronegative and equivocal, respectively. The level of antibodies against measles was associated with age of healthcare workers, but not with gender. All employees older than 60 years were measles seropositive, whereas those younger than 35 or within range 35 to 60 years of age had protective antibody titer in 77% and 95.5% of cases, respectively. The proportion of subjects with seronegative results did not depend on employee's position (doctor, nurse, cleaning worker), but varied a lot between different hospital departments. According to the data of logistic regression, the odds to have a seronegative test result among employees from somatic and remaining departments were 4.4-fold higher. Importantly, the rate of seronegative results was by 10-fold lower in employees born between 1968 and 1984 than those found in subjects born after 1985. On the other hand, subjects older than 60 years of age were seronegative at 50-fold lower rate than those who were under 35. The median concentration of measles immunoglobulin G among vaccinated healthcare workers vs. subjects recovered after natural infection was significantly lower reaching 0.56 IU/ml and 4.2 IU/ml (p < 0.001), respectively. Five-year monitoring showed that titer of measles IgG antibodies decreased by 1.2-1.9-fold (average — 1.5). Thus, a cohort of healthcare workers from multidisciplinary healthcare facility demonstrated that the proportion measles-susceptible subjects was 6.3%. Importantly, age of examined subjects mainly affected seronegative status. Taking into consideration age-related lowered serum antibody level in vaccinated healthcare workers, seroprevalence studies and subsequent revaccination of seronegative people should be performed at least once every 5 years to prevent measles spread in healthcare facilities.